TRUSTING THE STUDENTS AND EACH OTHER: A STORY OF CRITICAL COLLABORATIVE PRAXIS AND CRITICAL LITERACY PRACTICE IN AN URBAN U.S. CLASSROOM - Paugh, Patricia (Interfaces Científicas - Educação, 2018)
This article explores critical literacy practices that both emerged and were made visible through the collaborative praxis of an elementary teacher and a teacher educator, both working in a U.S. urban school context. Through shared investigations of classroom language and literacy pedagogy, the collaborators developed a mutual focus over several years that investigated possibilities for high-expectations academic learning when students were positioned students as active, democratic, and participatory knowledge generators who cared about learning and each other. The complementary roles and responsibilities taken up by each researcher that tap both personal and shared areas of expertise over a five-year cycle of critical collaborative praxis-oriented analysis are delineated. Two vignettes are shared using evidence from this analysis that demonstrates intersections between student learning as they take up writing and research related to their own critical purposes, as well as the learning of the research partners as they question and investigate theoretical contributions to their own teaching.